Adaptation as Migration - Thomas Leitch (Interfaces)
This essay explores the implications of using migration as a metaphor for adaptation. These implications become legally and morally fraught when adaptation is regarded not simply as migration but as emigration or immigration, two activities more narrowly defined by gatekeepers who are particularly invested in regulating and policing them. Drawing on examples from the Oz books by L. Frank Baum, the essay offers a preliminary grammar of adaptation as migration that emphasizes four areas: (1) foundational terms like host and target cultures, frames or scripts, and the parties involved in migrating and defining and regulating migration; (2) motives for migrating, encouraging migration, and inhibiting migration; (3) products of migrating; and (4) the morality and ethics of migration. It concludes by raising questions about the kinds of invisible migration that involve texts and utterances crossing borders which current theories of adaptation fail to take into account.